Stem cell-derived polarized hepatocytes - Dao Thi, Viet Loan; Wu, Xianfang; Belote, Rachel L.; Andreo, Ursula; Takacs, Constantin N.; Fernandez, Joseph P.; Vale Silva, Luis A.; Prallet, Sarah; Decker, Charlotte Caroline; Fu, Rebecca Menhua; Qu, Bingqian; Uryu, Kunihiro; et al. (Nature Communications, 2020)
Human stem cell-derived hepatocyte-like cells (HLCs) offer an attractive platform to study liver biology. Despite their numerous advantages, HLCs lack critical in vivo characteristics, including cell polarity. Here, we report a stem cell differentiation protocol that uses transwell filters to generate columnar polarized HLCs with clearly defined basolateral and apical membranes separated by tight junctions. We show that polarized HLCs secrete cargo directionally: Albumin, urea, and lipoproteins are secreted basolaterally, whereas bile acids are secreted apically. Further, we show that enterically transmitted hepatitis E virus (HEV) progeny particles are secreted basolaterally as quasi-enveloped particles and apically as naked virions, recapitulating essential steps of the natural infectious cycle in vivo. We also provide proof-of-concept that polarized HLCs can be used for pharmacokinetic and drug-drug interaction studies. This novel system provides a powerful tool to study hepatocyte biology, disease mechanisms, genetic variation, and drug metabolism in a more physiologically relevant setting.